U.P. handbuk ng kahandaan sa kalamidad - Paz, Consuelo J.; Zayas, Cynthia N. (U.P. Komite sa Pamamahala ng Krisis, sa pakikipagtulungan ng Sentro ng Wikang Pilipino, 1991)
A handbook that aims to collect data on earthquakes for the knowledge of the U.P community. It includes the profiles of different volcanoes in the Philippines and the things to be done in case of an earthquake.